ANALISIS GENDER TERHADAP KINERJA PEGAWAI DI KANTOR SEKRETARIAT DAERAH KOTA PALEMBANG - Marleni, Marleni (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
This study aims to determine the effect of Gender Analysis on Emplpyee Performance at the Regional Secretariat Office of North Palembang City. This research is a research with a totalquantative approach. The data used are primary data, with a total sample of 60 respndents, where this research was conducted for 2 months using a questionnaire to obtain the required data. Analysis of the influence of variables using simple linear regression gender analysis has a significant effect on employee performance.